Are frail patients more susceptible to intraoperative hypotension and 30-day mortality? - Fonseca, Diana (2022)
Introduction: Frailty has been considered to be an important predictor of surgical morbimortality, influencing both short and long-term postoperative mortality. Despite this association, less is known about frailty's impact in intraoperative hemodynamic stability, namely intraoperative hypotension, which may influence postoperative outcomes. We aimed to evaluate if frail patients submitted to elective surgery are more susceptible to experience intraoperative hypotension and mortality at 30 days. Methods: A prospective cohort study was conducted between March and November 2020. Fifty-three adult patients proposed for intermediate or high-risk surgery were enrolled. Frailty was assessed preoperatively by Clinical Frailty Scale. Intraoperative hypotension, defined by three different criteria, and mortality at 30 days were evaluated for each patient. Results: Of the 53 participants enrolled, 13.7% (n=7) were frail. All frail patients developed intraoperative hypotension by at least one of the criteria in contrast with 82.9% (n=29) of non-frail, although differences weren’t statistically significant (p=0.567). Intraoperative hypotension cumulative duration didn’t differ significantly between groups in generalized linear model. The 30-day survival rate was 96.2% and frailty had a significant influence on overall survival (p=<0.001). Conclusion: This study did not show an association between frailty and intraoperative hypotension development or it's cumulative duration. Though, it demonstrated that frailty, evaluated by Clinical Frailty Scale, is associated with decreased survival at 30 days postoperatively, which supports the routine use of this tool and outlights the importance of preoperative frailty screening.